Stability of $n-$ Dimensional Additive Functional Equation in Fuzzy Normed Spaces - Arasu, V.; Angayarkanni, M. (Sarajevo Journal of Mathematics, 2022)
In this paper, the authors investigate the generalized Hyers-Ulam-stability of new $n-$ dimensional additive functional equation \[ \sum_{j=1}^n f\left(-x_j+\sum_{1\leq i\leq n, i eq j} x_{i}\right)=(n-2)\sum_{j=1}^n f(x_j) \] in fuzzy normed space using direct and fixed point approach.